Evolution of methods of uranostaphyloplasty exemplified by the analysis of 1118 primary operations for congenital palatal defects - L. V. Kharkov (Blackwell Synergy, 2000)
The aim of surgical repair of congenital palatal clefts (uranostaphyloplasty) is two-fold. The first consideration is the functional result – the achievement of normal speech. The second is the avoidance of postoperative maxillary deformity.